Endoscopic Ex Vivo Evaluation of Bile Concentrations by Narrow Band Imaging: A Pilot Study - Roberta Maselli; Haruhiro Inoue; Haruo Ikeda; Manabu Onimaru; Akira Yoshida; Esperanza Grace Santi; Hiroki Sato; Nikolas Eleftheriadis; Shin-ei Kudo (Gastroenterology Research and Practice)
Background. Bile juice plays a major role in duodenogastroesophageal reflux (DGERD). Several devices to directly measure the bile concentration have been proposed. We aimed to ex-vivo evaluate the bile concentration by narrow band imaging (NBI). Method. From six surgical cholecystectomies, the content of the gallbladders was aspirated and the total biliary acid (TBA) concentration was evaluated. 2 mL was employed for serial twofold dilutions. Each dilution was scoped. Images on white light (WL) and NBI were captured and grouped accordingly to NBI-appearance and TBA-concentration. Results. Nondiluted bile had a TBA-concentration of 61965 ± 32989 μmol/L. Final dilution (1 : 4096) had 1.16 μmol/L. NBI and correspondent WL images were grouped into seven groups, and an NBI/Bile scale was created. Conclusion. The scale showed that not only NBI scale but also white light scale could be useful to predict the bile concentration. This initial study shows that NBI has a potential role in the detection of DGERD and further investigation is warranted to distinguish the presence and the concentration of bile, especially at very low TBA concentrations.